Nationwide molecular epidemiology of carbapenemase-producing Citrobacter spp. in France in 2019 and 2020 - Laura Biez; Rémy A. Bonnin; Cecile Emeraud; Aurélien Birer; Agnès B. Jousset; Thierry Naas; Laurent Dortet (mSphere, 2023)
ABSTRACTCarbapenemase-producing Enterobacterales have emerged in the last decades as one of the main threats in modern medicine. Enterobacter is a genus increasingly recognized as a key player in carbapenemase diffusion besides Escherichia coli and Klebsiella pneumoniae, but information regarding Citrobacter spp. remained scarce. A collection of 803 isolates of Citrobacter spp. recovered from the French National Center for carbapenem resistance over a 2-year period during 2019–2020 was analyzed. A total of 15 different carbapenemases were identified of which OXA-48 followed by NDM-1 and OXA-181 represented the main enzymes. Phylogenetic analysis of this collection revealed that Citrobacter freundii was the main species among which three main clones are circulating in France, being ST8, ST22, and ST91. ST22 and ST8 were distributed in all regions whereas ST91 demonstrated a regional spread. Analysis of the species diversity revealed that among the C. freundii complex, Citrobacter portucalensis and Citrobacter braakii were also disseminated. We revealed the dissemination of a clone carrying both blaDHA-15 (β-lactamase-encoding gene rarely reported in Enterobacterales) and blaOXA-48 in the north of France and allowed to identify an outbreak not previously investigated. This study analyzed the largest collection of carbapenemase-producing Citrobacter spp. and allowed deciphering of molecular epidemiology of Citrobacter spp. in France.IMPORTANCEThe emergence of carbapenemase producers in Enterobacterales mostly involves Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae complex species. However, in France, we observed the emergence and the rapid dissemination of carbapenemase in Citrobacter spp. In this study, we demonstrated that a wide variety of carbapenemases is produced by many different species of Citrobacter spp. However, we clearly identify three high-risk clones of Citrobacter freundii, ST8, ST22, and ST91 that drive the spread of carbapenemase in France. This epidemiological study paves the way of further analysis that would aim to identify the virulence factors involved in this pellicular ability of these three clones to disseminate at the hospital.